Assessment of the interaction procedure between Pt(IV) prodrug [Pt(5, 5′-dmbpy)Cl4 and human serum albumin: Combination of spectroscopic and molecular modeling technique. Issue 14 (26th October 2017) - Shahraki, Somaye; Saeidifar, Maryam; Shiri, Fereshteh; Heidari, Ameneh
Abstract : In this study, a cytotoxic Pt(IV) complex [Pt(5, 5′-dmbpy)Cl4 (5, 5′-dmbpy is 5, 5′-dimethyl-2, 2′-bipyridine) was selected to investigate its affinity to human serum albumin (HSA) by spectroscopy and molecular docking methods. This complex has a bidentate nitrogen donor ligand with four chloride anions attached to a Pt(IV) metal in a distorted octahedral environment. The ﬂuorescence data showed this complex quench the intrinsic ﬂuorescence of HSA through a static quenching mechanism. The binding constant ( K b ) and the number of binding sites ( n ) were obtained based on the results of fluorescence measurements. UV–vis, circular dichroism spectroscopy, and three-dimensional fluorescence spectroscopy proved that the Pt(IV) complex could slightly change the secondary structure of protein. Thermodynamic parameters show that the Pt(IV) complex binds to HSA through electrostatic and Vander Waals interactions with one binding site. The molecular docking results confirmed the spectroscopic results and showed that Pt(IV) complex is embedded into subdomain IIA of protein. The aim of this study is to describe the performance of effective anti-cancer drugs when faced with proteins such as HSA.